2013
DOI: 10.1002/macp.201300288
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Metallo‐Supramolecular Micellar Gels

Abstract: A small-angle neutron scattering investigation of metallo-supramolecular micellar gels built from polystyrene-block -poly( tert -butylacrylate) PS-b -PtBA-tpy (-tpy: terpyridine) block copolymers and transition metal ions is presented. The infl uence of the copolymer concentration on the structure and spatial organization of the micelles, as well as the impact of the subsequent addition of metal ions (Fe(II), Ni(II), and Zn(II)) on these characteristics is extensively studied. The experimental scattering cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Furthermore, stimuli-responsive properties can be bestowed to the self-assembled materials by the use of environmentally sensitive polymer sequences as one of the block . At the cutting edge of those research fields, coordination micellar gels have emerged as an intermediate category, combining the flexibility and responsiveness of both hydrophobic and metal–ligand associations …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, stimuli-responsive properties can be bestowed to the self-assembled materials by the use of environmentally sensitive polymer sequences as one of the block . At the cutting edge of those research fields, coordination micellar gels have emerged as an intermediate category, combining the flexibility and responsiveness of both hydrophobic and metal–ligand associations …”
Section: Introductionmentioning
confidence: 99%
“…The Cu-tethered metal complexes were shown to be active catalysts for the 1,3-dipolar cycloaddition of azide and alkynes to form 1, 2, 3 triazoles by "click" chemistry [221] while the Pd-based nanostructures could find applications as pseudo-homogeneous supported catalysts for Heck coupling reactions [222]. In a related example, Mugemana et al reported the synthesis of metallo-supramolecular gels based on transition metal ions and block copolymers [223]. First, PS-b-PtBA diblock copolymers bearing terpyridine chain end groups were prepared by using NMP followed by their self assembly in ethanol to generate micelles with a PS core and a PtBA corona.…”
Section: Absorbancementioning
confidence: 99%
“…[18][19][20] Among multitopic polymeric ligands, block copolymer micelles bearing ligands at the surface constitute a powerful approach to tune the rheological properties and responsiveness of soft materials. 3,[21][22][23][24][25][26][27][28] In this case, metallo-supramolecular micellar networks are obtained by a two-step process: (1) the self-assembly of block copolymers followed by (2) metal-ligand interactions. The first step corresponding to the self-assembly is achieved by dissolution of a block copolymer in a selective solvent of one block, leading to micelles bearing ligands at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Gohy's group developed this second strategy to trigger metallo-supramolecular polymer networks based on copolymeric micelles. 3,[21][22][23][24][25][26][27] Their studies involved a diblock copolymer based on polystyrene and poly (tert-butylacrylate) bearing a terpyridine ligand (Tpy) moiety at the chain-end (PS-b-PtBA-Tpy) which, in the presence of metal ions, yielded flower-like micelles and micellar gels in diluted and concentrated solvents, respectively. 3,21,22 Then, Piogé et al investigated stimuli-responsive metallo-supramolecular micelles starting from terpyridine-functionalized diblock copolymers based on PS and poly(N-isopropylacrylamide) (PS-b-PNIPAM-Tpy).…”
Section: Introductionmentioning
confidence: 99%